2018
DOI: 10.17559/tv-20170223093448
|View full text |Cite
|
Sign up to set email alerts
|

Noise in the Cabin of Agricultural Tractors

Abstract: This paper represents the results of the research of generated noise levels measured in three different years (2010, 2013, and 2015), in accordance with the proscribed norms HRN ISO 6394, HRN ISO 6396 and HRN ISO 5131. The research was conducted on test sites of Belje d.d. company. The measurement was carried out on three tractors of the FENDT model 410 with the aim of determining the increase of generated noise relative to the time the tractors spent in exploitation. The obtained results showed that none of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Singh et al [29] stated that the coefficient of determination ranged from 0.82 to 0.90 (which is a similar case here as well) and highlighted the speed of movement as a variable with significant impact on ergonomic factors. Furthermore, Lashgari and Maleki [40], in their study of the influence of different speeds when mowing grass with a tractor mower on the produced noise level, stated that the coefficient of determination R 2 was 0.957, which is also the case in the research of Barac et al [19], where noise was measured at the operator's workplace in relation to the age of the tractor. In the aforementioned research, a lower coefficient of determination (R 2 = 0.675), was achieved.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Singh et al [29] stated that the coefficient of determination ranged from 0.82 to 0.90 (which is a similar case here as well) and highlighted the speed of movement as a variable with significant impact on ergonomic factors. Furthermore, Lashgari and Maleki [40], in their study of the influence of different speeds when mowing grass with a tractor mower on the produced noise level, stated that the coefficient of determination R 2 was 0.957, which is also the case in the research of Barac et al [19], where noise was measured at the operator's workplace in relation to the age of the tractor. In the aforementioned research, a lower coefficient of determination (R 2 = 0.675), was achieved.…”
Section: Resultsmentioning
confidence: 80%
“…The tests were performed according to standards that considered internal noise measurements during movement, and the tractor had 5800 operating hours at the time of measurement. Barač et al [18,19] conducted noise level measurement during operation (when standing and moving) on three FENDT tractors (model 410). During the exploitation experiment, the tractors performed similar agrotechnical operations and had the same number of working hours.…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that the interior noise level of the cab was moderated by using adequate absorbing and isolating materials for a defined frequency range, and lower interior noise levels were achieved by using elastic suspension between the tractor chassis and the cab. Analyzing the interior noise levels in cab tractors over three different manufactured years, Barač et al (2018) showed that none produced a higher noise level than the permitted 90 dB.…”
Section: Introductionmentioning
confidence: 99%
“…They experimentally verified a defined vibration model and a parametric analysis. Barač et al [9] researched generated noise in the cabin of agricultural tractors. Caresta et al [10] study a relationship between natural frequencies and a pull out force for plates with two clamped edges.…”
Section: Introductionmentioning
confidence: 99%